2020
DOI: 10.1007/978-3-030-62056-1_45
|View full text |Cite
|
Sign up to set email alerts
|

Using AI-Enhanced Social Robots to Improve Children’s Healthcare Experiences

Abstract: This paper describes a new research project that aims to develop an autonomous and responsive social robot designed to help children cope with painful procedures in hospital emergency departments. While this is an application domain where psychological interventions have been previously demonstrated to be effective at reducing pain and distress using a variety of devices and techniques, in recent years, social robots have been trialled in this area with promising initial results. However, until now, the social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…This platform has been widely used in child-robot interaction studies [7,12,13,16]. Details of the overall project methodology have been previously published [17]. This current study specifically aimed to characterize children’s and caregivers’ (a) experiences of IVI-related pain and distress and (b) their perspectives surrounding integration of robots and AI within the pediatric healthcare context, to inform the design of this system.…”
Section: Introductionmentioning
confidence: 99%
“…This platform has been widely used in child-robot interaction studies [7,12,13,16]. Details of the overall project methodology have been previously published [17]. This current study specifically aimed to characterize children’s and caregivers’ (a) experiences of IVI-related pain and distress and (b) their perspectives surrounding integration of robots and AI within the pediatric healthcare context, to inform the design of this system.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that social robots can be used to manage child pain and distress during medical procedures (Ali et al 2019;Trost et al 2019). We are part of a team developing a social robot underpinned by a planning system to be used in this setting (Foster et al 2020;Lindsay et al 2022). The scenario presents a significant challenge for a social robot: the system must coexist with multiple humans engaged in numerous high-priority and dynamic tasks.…”
Section: A Clinical Setting Scenariomentioning
confidence: 99%
“…2) Safeguarding a User-Centric Approach in Healthcare: Indeed, HRI does not have to include an AI-systemic interaction in terms of adaptability and learning, facial recognition or predictive abilities. However, the future social robotics definitely will integrate more AI-methodologies [61]. Therefore, the notions of governance of robots in diagnostic care would benefit from an inclusion of contemporary ideas on AI governance.…”
Section: Robot Governance and Gender Fairnessmentioning
confidence: 99%